Polymers for sustained release formulations of dipyridamole-alginate microspheres and tabletted microspheres - (:unkn) unknown (My University, 1999)
The preparation of dipyridamole (DIP) alginate (alg) microspheres by different methods or the incorporation of tragacanth (trgh), pectin or Eudragit L-100 55 (Eud) in alg microsphere formulations did not provide a prolonged release of DIP at pH 1.2. Tabletted microsphere formulations containing alg, trgh, pectin, sodium carboxymethyl cellulose (CMC), sodium starch glycolate (SSG), carrageenan (carrg) or Eud as diluents in different ratios, produced tablets with good physical properties which did prolong DIP release. The type, viscosity and the ratio of the diluent polymer, microsphere size and the compression pressure were found to be important factors to produce tablets with desired properties. No advantage of the tablets containing alg microspheres and granulated diluents was observed over the tablets containing powdered diluents.
Keywords: Alginate; Carrageenan; Dipyridamole; Eudragit; Hydroxypropylmethyl cellulose; Microspheres; Pectin; Sodium carboxymethyl cellulose; Sodium starch glycolate; Tabletted microspheres; Tragacanth